Kallikrein 4 and matrix metalloproteinase-20 immunoexpression in malignant, benign and infiltrative odontogenic tumors - Crivelini, Marcelo Macedo [UNESP]; Oliveira, Denise Tostes; De Mesquita, Ricardo Alves; De Sousa, Suzana Cantanhede Orsini Machado; Loyola, Adriano Motta (Wolters Kluwer, 2016)
Context: Matrix metalloproteinase-20 (MMP20) (enamelysin) and kallikrein 4 (KLK4) are enzymes secreted by ameloblasts that play an important role in enamel matrix degradation during amelogenesis. However, studies have shown that neoplastic cells can produce such enzymes, which may affect the tumor infiltrative and metastatic behaviors. Aims: The aim of this study is to assess the biological role of MMP20 and KLK4 in odontogenic tumors. Materials and Methods: The enzymes were analyzed immunohistochemically in ameloblastoma, adenomatoid odontogenic tumor (AOT), calcifying epithelial odontogenic tumor, keratocystic odontogenic tumor with or without recurrence and odontogenic carcinoma. Statistical Analysis Used: Clinicopathological parameters were statistically correlated with protein expression using the Fisher's exact test. Kruskal-Wallis and Wilcoxon-independent methods were used to evaluate the differences in median values. Results: Positive Immunoexpression was detected in all benign lesions, with a prevalence of 75-100% immunolabeled cells. Patients were predominantly young, Caucasian, female, with slow-growing tumors located in the mandible causing asymptomatic swelling. No KLK4 expression was seen in carcinomas, and the amount of MMP20-positive cells varied between 20% and 80%. Rapid evolution, recurrence and age >60 years characterized the malignant nature of these lesions. Conclusions: Data showed that KLK4 and MMP20 enzymes may not be crucial to tumoral infiltrative capacity, especially in malignant tumors, considering the diversity and peculiarity of these lesions. The significant immunoexpression in benign lesions, remarkably in AOT, is likely associated with differentiated tumor cells that can produce and degrade enamel matrix-like substances. This would be expected since the histogenesis of odontogenic tumors commonly comes from epithelium that recently performed a secretory activity in tooth formation.
Keywords: KLK 4; MMP 20; odontogenic tumors